Characterizing meso- to submesoscale features in the South China Sea. (October 2020) - Lin, Hongyang; Liu, Zhiyu; Hu, Jianyu; Menemenlis, Dimitris; Huang, Yongxiang
Highlights: The SCS is rich in submesoscale features with significant seasonality in many regions; Predominant positive ζ is found except in regions with strong flow-topography interactions; Vertical motions in the upper SCS are dominated by tidal modulations; Horizontal KE spectra scale as k −2 for wavelength <100 km in both winter and summer. Abstract: In this study the mesoscale and submesoscale features in the South China Sea (SCS) are characterized based on a submesoscale-permitting numerical simulation (MITgcm llc4320) with nominal horizontal grid spacing of 1/48° ( 2.2 km in the SCS). The simulation includes tidal forcing, which is particularly crucial in the SCS where tides play a key role in many aspects of regional dynamics. Evaluation against observations demonstrates that the simulation is capable of reproducing a wide spectrum of dynamical features in the SCS. The simulation is then used to characterize meso- to submesoscale features in the SCS and the key findings are summarized as follows: (i) the SCS is rich in submesoscale features (e.g., vortices, filaments), which undergo significant seasonal variations in many regions; (ii) there is a clear dominance of positive surface relative vorticity ( ζ ) in most regions of the SCS presumably due to the centrifugal instability, but large negative ζ also emerges in areas with strong flow-topography interactions; (iii) the vertical motions in the upper SCS are dominated by tidal modulations with strong vertical velocities up to 0.01 m s −1, about an order of magnitude larger than those due to the quasi-balanced sub-inertial motions; and (iv) both the wintertime and summertime horizontal wavenumber spectra of kinetic energy scale roughly as k −2 (with k being the horizontal wavenumber) for wavelengths below 100 km. In addition, four key regions are highlighted with distinctive characteristics of submesoscale turbulence, including the northern SCS, Luzon Strait, the SCS western boundary current region in winter, and east of Vietnam in summer. A number of model deficiencies are noted, along with suggestions for improving model accuracy in order to better characterize the local submesoscale features as well as the underlying dynamics.